Whose Authority? Contesting and Negotiating the Idea of a Legitimate Interpretation of Islamic Law in Indonesia. Issue 2 (23rd March 2016) - Alfitri,
Abstract: This article examines the history of the evolution of Islamic legal authority in Indonesia and provides an account of how it is contested and negotiated in contemporary Indonesia, using the history of family law reform as an example. There is a plurality of sources of authority for Islamic law as they operate within the domain of family law. The case studies reveal tensions between continuity and change in the development of Islamic legal principles and the strategies that different actors employ to advance their preferred version of Islamic legal norms: while the state has adopted a synthetic approach in order to accommodate these multiple legal authorities and increase the efficacy of its own statutes, the ulama persistently insist on the authority of fiqh as the immutable point of reference in resolving legal problems faced by Muslims. These conflicts ensure that the statutes will continue facing challenges as a legitimate interpretation of Islamic law in Indonesia.